Pengaruh Persepsi Harga dan Kualitas Produk terhadap Kepuasan Konsumen : Survei pada Konsumen Erha Skincare di Kota Tasikmalaya - Hema Hayati (CV. Ulil Albab Corp, 2022)
The purpose of this study was to determine and analyze the effect of price perception and product quality on consumer satisfaction at Erha Skincare Tasikmalaya. The research method used is a survey method, while the population in this study are all Erha Skincare consumers in the City of Tasikmalaya who have made a purchase. Data were obtained directly through questionnaires to 100 respondents and multiple regression analysis methods. The results of this study indicate that price perception and product quality simultaneously have a significant effect on Erha Skincare Consumer Satisfaction in Tasikmalaya City.